INFORMATION AND COMMUNICATION TECHNOLOGIES FOR DEVELOPING CREATIVE COMPETENCE IN THE PROCESS OF OPEN TEACHING PHYSICS AND MATHS - Makhmudova, Dilfuza Melievna; Tadjibaev, Bakhrom Ruzievich; Dusmurodova, Gavhar Kholboevna; Yuldasheva, Gulshad Tileuovna (International Journal of Psychosocial Rehabilitation, 2020)
This article is written with the goal of theoretically substantiating the use of information and communication technologies in the process of open teaching physics and maths. The following tasks were identified and solved: to determine the role of information and communication technologies in the formation and achievement of the goals of modern physical education, indicators of its quality and effectiveness; analyze the state of physical education and the opportunities that ICTs provide in raising its level; to develop a model of an open learning system that uses information and communication tools and meets the target orientation of the concept and methodology of physical education; to develop the principles of designing electronic educational and methodological complexes and implement them in the creation of complexes for the general course of physics and maths and special physical disciplines intended for open training in physics and maths; provide the open physics and maths teaching system with the necessary software and methodological tools; to reveal the possibilities of educational and research activities of students based on the use of ICTs in the open physics and maths teaching system; check the ef ectiveness of the open physics and maths teaching system.